Variants Of Clinical Manifestations Of Giardiasis In Children (Eurasian Medical Research Periodical, 2024)
Clinical manifestations of giardiasis are varied, but lesions of the gastrointestinal tract prevail, which is associated with the localization of parasites in the duodenum and jejunum. Along with severe clinical manifestations of giardiasis, latent forms are also described. Isolation of Giardia without clinical manifestations is often used as an argument for assessing this condition as a healthy carriage of protozoa. Under our supervision there were 36 children with latent, 78 children with subclinical and 62 with clinical forms of giardiasis. The children were examined at the Samarkand Multidisciplinary Children's Medical Center. The age of the children ranged from 3 to 15 years. Diagnosis of giardiasis was based on complaints, anamnesis, clinical manifestations of giardiasis, as well as an expanded coprogram for the determination of protozoa in feces using the formalin-ether enrichment method. Giardiasis, especially in children, is clinically manifested in a variety of forms - from pure giardia carriers to severe forms. It is clinically advisable to distinguish latent, subclinical and clinical forms of giardiasis, because Along with a single anti-giardiasis drug therapy, dietary treatment is required.